(untitled) (Al-Academy, 2024)
The environmental concept has come to frame contemporary compatibility relations in interior design, through the prioritization of the physical use of natural components and systems contained in the environment (including means of ecological integration). Artistic and creative treatments are constructed according to design outputs that include functional needs data. The interior and nature of living components and the resulting frequencies to achieve interspace (ecological) harmony and adaptation reflect natural and man-made environmental sustainability.